Does Conservatism Matter? A Time Series Approach to Central Banking - Helge Berger; Ulrich Woitek (Center for Economic Studies and ifo Institute (CESifo), 1999)
The empirical literature on central banking has found measures of central bank independence/conservatism to be negatively correlated with inflation and inflation variance across countries. But the cross-country approach has been criticised for its focus on policy outcomes instead of policies, and for the unsystematic conflation of the concepts of independence and conservatism. We avoid these shortcomings by estimating a single-country time series model for the German Bundesbank. We find that an increase in central bank conservatism leads to higher short-term interest rates and a more activist stabilisation policy with respect to macroeconomic shocks. More conservative Bundesbank regimes are associated with a less volatile economy, higher output and somewhat lower inflation. We also investigate the interaction between the central bank and the government. It turns out that non-conservative Bundesbank Councils react more strongly to macroeconomic shocks under conservative than under non-conservative government regimes.
Keywords: 330; Central Bank Independence and Conservatism; Monetary Policy; Central Bank Government Relations; Generalised Impulse Responses